Pengaruh Kualitas Pelayanan Publik, Sarana Prasarana Publik Dan Kinerja Pegawai Terhadap Kepuasan Masyarakat Pada Pelayanan E-KTP Di Kantor Camat Ampek Angkek Kabupaten Agam - Febri Suci, Arfita; Ajidin, Asep (CV. ITTC INDONESIA, 2023)
This study aims to determine and analyze the effect of the quality of public services, public infrastructure and employee performance on community satisfaction in the E-KTP service at the Ampek Angkek Sub-District Office, Agam Regency. This type of research is associative descriptive analysis. The population in this study is all people who manage E-KTP who have not recorded their E-KTP. The sample used was 100 people who took care of the E-KTP and used a proportional random sampling technique. Primary data is the type of data used in this study. Data processing using SPSS 24. Data collection techniques using a questionnaire. The collected data was examined using descriptive analysis. Multiple regression analysis in research. Based on the research findings, it is known that the quality of public services (X1) is 0.017 <0.05. The significance of facilities and infrastructure (X2) is 0.024 <0.05 and employee performance (X3) is 0.000 <0.05 (Ho is rejected Ha is accepted). This illustrates that employee performance has a significant influence on community satisfaction managing e-KTP services at the Ampek Angkek Sub-District Office.